PERSEPSI GURU PAMONG TERHADAP KOMPETENSI MAHASISWA PPL JURUSAN TADRIS MATEMATIKA IAIN LHOKSEUMAWE - Abdul Kadir (Jurnal Numeracy, 2019)
This study aims to describe the perception of tutor teachers on the competence of PPL students in the Mathematics Department Tadris IAIN Lhokseumawe. Competencies reviewed include pedagogical competencies, personality competencies, professional competencies and social competencies. This study uses a quantitative descriptive research approach with a type of survey research. The population in this study were junior high school / MTs teachers and high school / MA in Lhokseumawe City and North Aceh. The sample in this study were 13 tutors. Data collection is done by distributing Likert scale questionnaires to tutor teachers. The data analysis technique uses descriptive statistics. From the results of data analysis, it was found that pedagogical competence of PPL students was in good criteria with a percentage of 81.77%, professional competency was in good criteria with a percentage of 79.23%, personality competencies were very good criteria with a percentage of 88.46% and student social competence The PPL majoring in mathematics is very good with a percentage of 87.43%. Based on these results the competence of PPL students majoring in mathematics is classified as a good percentage. Abstrak Penelitian ini bertujuan untuk mendeskripsikan persepsi guru pamong terhadap kompetensi mahasiswa PPL Jurusan Tadris Matematika IAIN Lhokseumawe. Kompetensi yang ditinjau meliputi kompetensi pedagogik, kompetensi kepribadian, kompetensi profesional dan kompetensi sosial. Penelitian ini menggunakan pendekatan penelitian kuantitatif deskriptif dengan jenis penelitian survey. Populasi dalam penelitian ini adalah guru pamong SMP/MTs dan SMA/MA Kota Lhokseumawe dan Aceh Utara. Sampel dalam penelitian ini sebanyak 13 guru pamong. Pengumpulan data dilakukan dengan menyebarkan angket skala likert kepada guru pamong. Teknik analisis data menggunakan statistik deskriptif. Dari hasil analisis data diperoleh bahwa kompetensi pedagogik mahasiswa PPL berada dalam kriteria baik dengan persentase 81,77%, Kompetensi profesional berada pada kriteria baik dengan persentase 79,23%, Kompetensi kepribadian berada kriteria sangat baik dengan persentase 88,46% dan kompetensi sosial mahasiswa PPL jurusan tadris matematika berada pada kriteria sangat baik dengan persentase 87,43%. Berdasarkan hasil tersebut kompetensi mahasiswa PPL jurusan tadris matematika tergolong dalam persentase yang baik. Kata kunci: Persepsi, Kompetensi Guru, Praktek Pengalaman Lapangan